Analysis of men's professional tennis singles match data and strategies - a case study of 2022 and 2023 ATP year-end finals - Li, C.-H.; Huang, C.-F.; Chang, J.-H. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
This study analyzed serve and serve return performance in the 2022 and 2023 ATP Year-End Tennis Championships, focusing on player rankings. The post-match data is compared between the top and bottom 4 players, examining differences in the top 4 rankings for both 2022 and 2023. Two-way ANOVA was used to examine the differences in "service and serve return " across different years and rankings, with a significance level set at a =.05. The key factors for winning in tennis include serve speed, average second serve speed, and scoring rates on both first and second serves. Top 4 ranked players achieved success by reducing serve speed for strategic adjustment, while improving second serve speed in 2023. This tactic reduces opponent's chances of successful serve returns, emphasizing the importance of applying pressure in both first and second serve returns.